2017
DOI: 10.1002/pssa.201700238
|View full text |Cite
|
Sign up to set email alerts
|

Deep carrier traps in as grown isotopically pure 28Si FZ crystal

Abstract: We studied a distribution of dopants and carrier traps in the FZ grown 28 Si crystal. Samples cut-out from various parts of an as-grown crystal were analysed by deep level transient spectroscopy (DLTS) and photoluminescence (PL). Several traps were detected at the concentration level of $10 10 cm À3 by DLTS. Careful analyses of the obtained signals allow attributing the related traps to agglomerates of intrinsic defects. A correlation of the trap concentration to the phosphorus doping, detected by PL and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…These observations can be correlated with previously reported degradation mechanisms, and with induced carrier traps in FZ‐Si annealed at higher temperatures . Very similar traps were also observed in FZ‐Si crystals that were quenched to room temperature from 800 °C after crystal growth . Recently, it was reported that the preannealing of mc‐Si cells in the dark at temperatures of 75–170 °C for several hours causes a degradation of the cell efficiency and affects further the LeTID process .…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…These observations can be correlated with previously reported degradation mechanisms, and with induced carrier traps in FZ‐Si annealed at higher temperatures . Very similar traps were also observed in FZ‐Si crystals that were quenched to room temperature from 800 °C after crystal growth . Recently, it was reported that the preannealing of mc‐Si cells in the dark at temperatures of 75–170 °C for several hours causes a degradation of the cell efficiency and affects further the LeTID process .…”
Section: Introductionsupporting
confidence: 88%
“…[24] Since the FZ-Si growth process excludes the incorporation of metal contaminants in significant concentrations, the origin of the traps is supposed to be related to the agglomerates of intrinsic defects (vacancies and/or interstitials) formed with participation/assistance of nitrogen and/or hydrogen. An increased defect concentration in FZ-Si crystals was detected at locations where dopant concentrations were higher (see previous studies [22,24,26] ). The similarity of LeTID-related defects to those formed in FZ-Si [17] may also originate from an enhanced density of intrinsic defects and dopants in striations of FZ-Si crystals.…”
Section: Trap Emission Activation Energy [Ev]mentioning
confidence: 71%
See 3 more Smart Citations